Hubungan Tingkat Pengetahuan Ibu Tentang Anemia dengan Kepatuhan Konsumsi Tablet Fe Tambah Darah pada Ibu Hamil di Wilayah Kerja Puskesmas Kota Selatan - Mohamad Reynaldi Muchsin; Siti Rahma; Sitti Fatimah M. Arsad (Lembaga Pengembangan Kinerja Dosen, 2026)
Red blood cell deficiency during pregnancy reflects a natural biological process that occurs as the body supports fertilization and embryo development. Pregnant women often experience low hemoglobin levels, typically around 11% in the first and third trimesters, or about 10.5 grams in the second trimester. Iron deficiency anemia arises mainly from inadequate iron intake and poor compliance with iron supplement consumption. The level of adherence among pregnant women is strongly influenced by their understanding of anemia and awareness of possible side effects of supplementation. This study aims to analyze the relationship between pregnant women’s knowledge about anemia and their compliance in consuming iron supplements to prevent anemia, focusing on the South City Community Health Center area. The research used a quantitative analytical survey with a cross-sectional design, involving 83 postpartum women selected through purposive sampling. Data were gathered using questionnaires, and the relationship between knowledge and compliance was tested using frequency distribution and chi-square analysis. The results revealed a significant correlation (p-value = 0.000), indicating that higher maternal understanding of anemia is associated with better adherence to iron supplement consumption among pregnant women in the study area.